Physical therapy of rotator cuff injuries of olympic weightlifters: A systematic literature review - Konjar, Janez; Arko, Živa (Annales Kinesiologiae, 2023)
From an injury-rate standpoint, Olympic weightlifting is a relatively safe sport. Despite that, a large number of repetitions, the ballistic nature of the lifts and the high forces sustained by the shoulder joint during their execution can lead to shoulder injuries, specifically rotator cuff injuries. The purpose of this paper was to investigate the scientifically proven physiotherapy methods and what their indications are when dealing with rotator cuff injuries of Olympic weightlifters. A qualitative literature review method was used, and the following online databases were included: PubMed, Scopus, Wiley, and PEDro in ResearchGate. The keywords in the literature search were: rotator cuff, shoulder, injury, physiotherapy, sport, weightlifting and Olympic weightlifting. The final analysis included fully published and accessible research papers in English from 2012 onwards, focusing on the physiotherapy of rotator cuff injuries. In total, 16 research papers were included in the final review. Management of rotator cuff injuries is a complex process, especially in sports with overhead movements. We found that the success and effectiveness of the physiotherapy process can be improved through a proper combination of kinesiotherapy, physical agent modalities, manual methods and other forms of therapy. The choice of the specific methods and their duration depends on the pathology of the individual injury. Further research focusing on Olympic weightlifting is needed to create precise and conclusive guidelines for rehabilitation, especially for sport specific phases occurring later in the rehabilitation process.